Hubungan Self-Esteem terhadap Level Kecemasan pada Mahasiswa Pogram Studi Pendidikan Agama Kristen [The Relationship of Self-Esteem to Anxiety Level in Christian Religious Studies Students] - Suparman Suparman (Universitas Pelita Harapan, 2019)
Levels of anxiety and self-esteem often affect students’ lives, even causing students to fail, unable to fulfil the academic requirements of lectures, and undergo the entire educational process. As a matter of fact, in general, students are not aware of this reality. Therefore, this study aims to find whether there is a relationship between the level of self-esteem and anxiety levels in Christian Religion Education students at UPH. In order to find the relationship between self-esteem and anxiety levels, this research is conducted in quantitative methods and the type of research is correlational. The sample is collecting between January and June 2019. As the results, students who classified as low self-esteem is 55% meanwhile 54% of students who have high levels of anxiety. The correlation between the two is -0.6. The negative correlation results indicate that the lower level of self-esteem will make the level of anxiety higher. The results of this study can be used to determine interventions, either through coaching, personal counselling, or through group therapy.